Comparative Anatomy of Maize and its Applications - Maiti, R. K.; Ghosh, S. K.; Koushik, S.; Ramasamy, A.; Rajkumar, D.; Vidyasagar, P. (International Journal of Bio-resource and Stress Management, 2011)
The present study reveals that there are large variations in anatomy of maize genotypes, which help in selecting drought tolerance lines, stem borer resistant as in tropical region. In some genotypes, presence of thick exodermis and higher lignification provide better structural integrity, and higher root diameter is associated with higher xylem diameter which helps in better solute transport. Considerable variations exist among genotypes in distribution and amount of mechanical tissue (stereome) and vascular bundles, and in the size and shape of the protoxylem cavity. In some genotypes, there is strong steroeme system in stem and long bulliform cells, thick sclerenchyma patches in leaf to survive in severe drought condition. Leaf anatomy possesses typical Kranz anatomy characteristics of C4 plant showing the variation in trichome density, silica crystal deposition on the epidermis which offers insect and fungal resistance. Maize genotypes show variability in seed anatomy with distribution and amount of corneous and floury endosperm which may be related to imbibitions capacity.